192. Evaluation of a commercial orthopedic metal artefact reduction tool in radiation therapy. (December 2018) - Manco, L.; Fabbri, S.; Landin, M.M.; Brigato, A.; Malorgio, A.; Fiorica, F.; Turra, A.
Abstract : Purpose: In radiotherapy process image artifacts can lead either a wrong definition of structure contours by the clinician either an erroneous computation of dose due to inaccuracies in the Hounsfield Unit (HU) values. Radiotherapy patients have often metal implants and this causes several image artifacts. This study is focused on the advantages using a commercial metal artifacts reduction algorithm, O-MAR (Philips Healthcare System, Cleveland, OH). Methods and materials: The study is performed on five head and neck cases with metal dental implants. Patients were scanned on a large bore CT Brilliance Philips. The scanned images were reconstructed with standard and O-MAR algorithm for each patient. The structures drawing by the clinicians on the O-MAR series were copied, on the originally CT images to evaluate the dose distribution on the same volume. The plans have been made on Pinnacle TPS in nine field steep and shoot intensity modulated radiation therapy (IMRT). The treatment provided two or three PTVs, respectively with 54/66 Gy and 54/60/66 Gy and constraints were evaluated on different OARs, close to the artifacts region, such as bone marrow, parotids, mandibule. Hounsfield Units (HU) variation were analyzed also in additional region of interest (ROI) near the dental implant. Results: In the OMAR images, noise values were generally reduced, standard deviation of HU is lower than standard images. Statistical analysis on HU values was performed, but without significant difference between the two data sets. Evaluating the dose distribution and the dose volume histogram (DVH) with the clinicians, no significant difference were detected. Conclusion: In head and neck case, when patients have dental implants, the use of O-MAR improve the entire radiation treatment planning process, especially for contouring because increase the accuracy of CT HU and reduce the noise. No significant changes in dose calculation had been found.